Human–environment interactions during the early mid-Holocene in coastal Ecuador as revealed by mangrove coring in Santa Elena Province. (August 2016) - Pearsall, Deborah M; Duncan, Neil A; Jones, John G; Friedel, Dorothy E; Veintimilla, Cesar I; Neff, Hector
Coastal environments of the early mid-Holocene provided challenges and opportunities for agriculturalists living in the Santa Elena Peninsula, Ecuador (Santa Elena Province, formerly southwestern Guayas Province). Cores extracted from swamps in three river outflows, namely, the Río Verde/Río Zapotal drainage (Chanduy estuary), the Río Grande (Punta Carnero locality), and the Río Valdivia, provided pollen, phytolith, sedimentary, and elemental sequences relevant to documenting vegetation and agriculture. The Chanduy record documented maize and other cultigens from 3200 to 500 cal. BC, providing evidence for intensive cultivation of alluvial lands. The Punta Carnero core provided the first evidence for occupation of the peninsula during the 'hiatus' between the Vegas and Valdivia periods, as maize was present in a stratum dating to 4857 cal. BC. Records documented mid-Holocene sea-level stabilization, development of low-energy depositional environments, and variation in rainfall attributable to El Niño-Southern Oscillation (ENSO) by 5000 cal. BC. There was no evidence that the region was either markedly wetter or drier in the early mid-Holocene, suggesting that climate controls similar to those of today were in place.